Joseph-Frédéric-Benoît Charrière - How to explain his success as one of the most famous surgical instrument makers regarding his life from childhood to death - Badawi, Jasmin Katrin (Urologia internationalis, 2017)
Introduction: We use the name "Charrière" every day as a unit of measurement. This article explains his success as one of the most famous instrument makers who ever lived. Materials and Methods: A review of the literature was completed using PubMed. Additionally, material of historical sources like the museum of Bulle was used. Results: Joseph-Frédéric-Benoît Charrière was born in Switzerland in 1803. At the age of 13, he moved to Paris and learned the profession of a cutler. In 1820, he took over the workshop of his teacher Vincent. Dupuytren was one of the most important people in Charrière's professional life. Charrière specialized in the fabrication of surgical instruments of such high quality that he was very sought after by famous surgeons. In 1837, Charrière went to Sheffield, England, to learn more about working with metals and alloys. In 1851, he was inducted into the Legion of Honour. Charrière died in 1876 in Paris. Conclusions: The patronage of Dupuytren was a very important supporting factor in Charrière's professional life, but mainly his great courage, the willingness to learn from others, his creativity and technical fantasy and his curiosity and broad interest in a lot of different fields explain his unmatched professional success.
Gesehen am 22.05.2018
Received: November 9,2015. Published online: November 25, 2016